Design and Development of a Mobile-Based Water Reminder Application on the iOS Platform - Supardianto, Supardianto; Mandasari, Devi (Journal of Applied Informatics and Computing, 2023)
Lifestyle encompasses the various ways in which individuals, groups, and nations are influenced by geography, economy, politics, history, culture, and religion. It reflects the characteristics of residents, including their daily behaviors in work, activities, and health. Maintaining a healthy lifestyle is crucial for overall well-being, and one key aspect is ensuring an adequate intake of water. Water constitutes the primary component of the human body, comprising an average of 70-80 percent of an individual's body weight. Factors influencing water consumption behavior include knowledge and preferences for other beverages. To address the challenge of promoting water consumption and advocating for its importance, this study proposes the development of a mobile application system capable of reminding individuals to drink water based on personalized needs, considering factors such as gender, age, weight, height, and activity level. The research aims to leverage and advance existing technology, specifically by creating a mobile application on the iOS platform. The objective is to enhance and reinforce individuals' discipline in maintaining proper water intake. Targeting users from middle-class to affluent social conditions, the application is tailored for the iOS platform. The study involves testing the functionality of the water reminder system software developed for mobile devices running on the iOS platform. The ultimate goal is to create an information system that not only exhibits maximum aesthetics and functionality but also adheres to the principles of interface design, including the application of the eight golden rules.